IMPLEMENTATION OF SOCIAL SERVICE AT THE AVALOKITESVARA VIHARA AS AN INSTRUMENT FOR ASSESSING THE QUALITY OF HEALTH SERVICES IN THE ASPECT OF HEALTH LAW - Riska Febria Afrila; Henry Aspan; Muhammad Arif Sahlepi (RADJA PUBLIKA, 2025)
Health services are one of the efforts undertaken to improve public welfare and constitutional rights guaranteed by the 1945 Constitution and regulated in Law No. 17 of 2023 concerning Health. Health social services organized by religious institutions such as the Avalokitesvara Temple have strategic potential as an instrument for assessing the quality of health worker services, but the legal aspects and quality assessment mechanisms have not been comprehensively studied. This study aims to analyze the implementation of social services at the Avalokitesvara Temple as an instrument for assessing the quality of health worker services from a health law perspective, including legal regulations, service quality standards, functions as an assessment instrument, and legal protection for health workers. The study uses an empirical juridical approach with primary data from observations and in-depth interviews with health workers, managers, and beneficiaries, as well as secondary data in the form of laws and academic literature analyzed descriptively and qualitatively with data triangulation. Social services at the Avalokitesvara Temple have a strong legal basis and apply the principle of non-discrimination by involving a competent multidisciplinary medical team. This activity has the potential to evaluate the professional competence, ethics, and communication of healthcare workers, but faces obstacles such as limited medical equipment, unintegrated documentation, and the absence of specific SOPs and standardized assessment instruments. Legal protection for healthcare workers is guaranteed through Article 83 of the 2023 Health Law and liability insurance. The study recommends the development of specific SOPs, standardized assessment instruments, improvements to technology-based documentation systems, and strengthening cross-sector collaboration to ensure legal certainty and improve the quality of community-based services.